Nanomaterials in Animal Husbandry: Research and Prospects - Wang, Kun; Lu, Xubin; Lu, Yi; Wang, Jiacheng; Lu, Qinyue; Cao, Xiang; Yang, Yi; Yang, Zhangping (Frontiers in Genetics, 2022)
Anti-inflammatory, antiviral, and anti-cancer treatments are potential applications of nanomaterials in biology. To explore the latest discoveries in nanotechnology, we reviewed the published literature, focusing on co-assembled nanoparticles for anti-inflammatory and anti-tumor properties, and their applications in animal husbandry. The results show that nanoparticles have significant anti-inflammation and anti-tumor effects, demonstrating broad application prospects in animal breeding. Furthermore, pooled evidence suggests that the mechanism is to have a positive impact on inflammation and tumors through the specific drug loading by indirectly or directly targeting the disease sites. Because the precise regulatory mechanism remains unclear, most studies have focused on regulating particular sites or even specific genes in the nucleus by targeting functional co-assembled nanoparticles. Hence, despite the intriguing scenarios for nanotechnology in farmed animals, most results cannot yet be translated into field applications. Overall, nanomaterials outperformed similar materials in terms of anti-inflammatory and anti-tumor. Nanotechnology also has promising applications in animal husbandry and veterinary care, and its application and development in animal husbandry remain an exciting area of research.